THE IMPACT OF ELECTRONIC DIGITAL SIGNATURE AND ITS USE ON MODERN LABOR ACTIVITY (Modern education and development, 2025)
:  In recent years, due to the rapid development of digitalization and information technologies, the use of  electronic digital signatures (EDS) in document circulation processes is becoming increasingly widespread. An electronic digital signature (EDS) is a set of digital data attached to an electronic document that confirms its authenticity, integrity, and authorship. This article analyzes the essence of  the EDS, its technological foundations, areas of application, and its impact on labor activity. It also highlights the socio-economic and legal consequences of the EDS system. The article presents a scientific approach to improving the modern document circulation system through the use of electronic signatures.